Methods of Strategic Planning in Management of ModernMunicipality - A E Tkachenko (RUDN Journal of Political Science, 2010)
In the given article the application of methods of strategic planning in management of municipality is analyzed. The article describes the urgency of development and passing of the strategic documents at all authority levels, and also points at problems interfering adoption of strategic planning in municipal practice.